2017
DOI: 10.1038/srep43832
|View full text |Cite
|
Sign up to set email alerts
|

Pupillary responses to short-wavelength light are preserved in aging

Abstract: With aging, less blue light reaches the retina due to gradual yellowing of the lens. This could result in reduced activation of blue light-sensitive melanopsin-containing retinal ganglion cells, which mediate non-visual light responses (e.g., the pupillary light reflex, melatonin suppression, and circadian resetting). Herein, we tested the hypothesis that older individuals show greater impairment of pupillary responses to blue light relative to red light. Dose-response curves for pupillary constriction to 469-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
37
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 65 publications
(82 reference statements)
8
37
0
2
Order By: Relevance
“…It could also be due to the difference in age between the two groups, as BPD decreases with ageing (Fotiou et al 2007). IpRGCs degenerate also with age (Lax et al 2016); however, pupillometric studies have shown that melanopsin-mediated PIPR does not change with age (Kankipati et al 2010;Herbst et al 2012;Rukmini, Milea, et al 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…It could also be due to the difference in age between the two groups, as BPD decreases with ageing (Fotiou et al 2007). IpRGCs degenerate also with age (Lax et al 2016); however, pupillometric studies have shown that melanopsin-mediated PIPR does not change with age (Kankipati et al 2010;Herbst et al 2012;Rukmini, Milea, et al 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…27 In principle, this approach, combined with chromatic light stimulations, elicits a sequential activation of rods, cones, and ipRGCs, and evaluates the functional integrity of the retina across a wide range of irradiances. 27 Although such a pupillometric screening method may not allow an isolated evaluation of the melanopsin-dependent intrinsic response of ipRGCs, it is not affected by mild and moderate cataracts, 32 and may provide a more detailed insight on the origin and magnitude of underlying neuroanatomic abnormalities, and detects subtle physiologic deficits that previous studies using continuous or pulses of full-field light stimulations failed to uncover in early-stage glaucoma. 22,24 In this study, the reduction in pupillary constriction amplitudes to moderate and high irradiances of blue light (above 11.0 Log photons/cm 2 /s) corresponding to the range of activation of ipRGCs 12 is indicative of altered intrinsic photosensitivity or a degeneration of these cells in earlystage POAG.…”
Section: Discussionmentioning
confidence: 99%
“…We here wish to entertain another scenario, because it has a scientific interest in its own right. Since Alice would still have to cooperate by properly responding to the light flash interrogations, in the event that she would not, Eve could resort to a more subtle approach and measure (with Alice either being conscious or sedated) Alice's pupillary light reflex [67][68][69][70][71], hoping to extract information on Alice's α-map. However, existing evidence suggest a higher detection threshold for the pupillary reflex, and in general, the relation of the physiological backgrounds of light perception and pupillary reflex is poorly understood.…”
Section: Discussionmentioning
confidence: 99%